CONCEPTIONS OF RATIONALITY AND ISLAMIC PHILOSOPHY OF EDUCATION: NAVIGATING TRADITION AND MODERN SCIENCE - Qureshi, Mohd Saif (Sekolah Tinggi Agama Islam Sadra, 2025)
This paper investigates the diverse conceptions of rationality within Islamic philosophy and their relevance to contemporary Islamic education, especially when considering modern scientific developments like evolution by natural selection, especially when connected with the development of Artificial Intelligence (AI) which is growing rapidly and starting to enter the world of education. The relationship between Islamic theology and scientific paradigms continues to be a topic of debate, which influences pedagogical approaches. A thorough understanding of the various Islamic rationalities, spanning from the early Islamic era to the classical period, is essential for creating an educational framework that promotes critical thinking while upholding Islamic values. Using a qualitative method, this writing examines the contributions of key figures such as al- Kindī, al-Farābī, Ibn Sīnā, al-Bīrūnī, al-Ghazālī, Ibn Tufayl, Ibn Rushd, Junayd al-Baghdādī, ‘Abd al-Qādir al-Jīlānī, Khwāja Mu‘īnuddīn Chishtī, and Jalāl al-Dīn Rūmī to illustrate the different forms of rational engagement in Islamic intellectual history. It is proposed that addressing the conflict between traditional Islamic teachings and modern scientific theories requires a reassessment of educational strategies and more expansive understanding of rationality itself.